2001
DOI: 10.1002/ijc.10171
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptors and proliferation in breast carcinomas of equivalent histologic grades in pre‐ and postmenopausal women

Abstract: Breast cancers in younger, premenopausal women are more likely to exhibit an adverse prognostic profile (including negative steroid hormone receptors and a high rate of cellular proliferation) and poor outcome than breast cancers in postmenopausal women. It has been hypothesized that this adverse prognostic profile is a result of the higher histologic grade of breast cancers in pre-compared with post-menopausal women. To assess the association of expression of steroid hormone receptors and indicators of prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 100 publications
(112 reference statements)
1
55
0
Order By: Relevance
“…The cytoplasmic staining was semi-quantified by an immunoscore that incorporated both the percentage of cells that stained as well as the intensity of staining. 39,40 Overall, mean immunoscores for GLI1, PTCH1 and SHH were increased 1.8-, 1.9-and 2.9-fold, respectively, in cancer epithelial cells in comparison to corresponding normal epithelium (Fig. 2B and Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…The cytoplasmic staining was semi-quantified by an immunoscore that incorporated both the percentage of cells that stained as well as the intensity of staining. 39,40 Overall, mean immunoscores for GLI1, PTCH1 and SHH were increased 1.8-, 1.9-and 2.9-fold, respectively, in cancer epithelial cells in comparison to corresponding normal epithelium (Fig. 2B and Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…First, the optimal cut-off level for Ki67 expression in breast cancer has not yet been universally established. Some authors defined 20% or more Ki67 staining as a high expression level, while others justified the median value of percent positively stained cells as the distinguishing value to segregate high expression from low (Spyratos et al, 2002;Talley et al, 2002). Herein, 20% staining was defined as the cut-off value for Ki67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…2 This has traditionally taken the form of mitotic activity scoring, which is an integral component of histologic grading, an established prognostic marker in breast cancer. 20 While the role of Ki67 immunohistochemistry as a prognostic and predictive marker in breast cancer has been widely investigated, 5,6,8,[21][22][23][24][25] staining thresholds and cutoffs have been mostly arbitrary and are not universally standardized. Percent positively stained nuclei, 26,27 number of nuclei stained per 10 high power fields, 5 stratification of MIB-1 staining in tertiles 8 have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors use Ki67 staining of 20% or more to define a high level, 6 while others advocate segregating high from low staining via the median of positively stained cells as the distinguishing value. 25 Recently, Spyratos et al 7 have suggested that the optimal threshold level should be 25% based on multivariate analyses of MIB-1 immunostaining at different cutoffs. Additional variation issues include selection of the appropriate area for evaluation of immunostaining, be it the center or periphery of the tumor; area of highest cell density; or zone of highest tumor cell immunohistochemical reactivity.…”
Section: Discussionmentioning
confidence: 99%